Knowledge, Attitude, and Prescription Practice on Antimicrobials Use Among Physicians: A Cross-Sectional Study in Eastern China. (10th December 2021) - Xu, Rixiang; Mu, Tingyu; Jian, Wang; Xu, Caiming; Shi, Jing
Over-prescription of antimicrobials for patients is a major driver of bacterial resistance. The aim of the present study was to assess the knowledge, attitude, and prescription practices regarding antimicrobials among physicians in the Zhejiang province in China, and identify the determining factors. A total of 600 physicians in public county hospitals and township health institutions were surveyed cross-sectionally using a structured electronic questionnaire. The questionnaire was completed by 580 physicians and the response rate was 96.67%. The mean score of 11 terms related to antimicrobial knowledge was 6.81, and an average of 32.1% of patients with upper respiratory tract infections (URTIs) were prescribed antimicrobials. Multivariate analysis indicated that young general practitioners with less training are more likely to contribute to more frequent antimicrobial prescriptions ( P < .05). In contrast, older physicians with more training are more willing to provide patients with the correct knowledge regarding antimicrobials and less likely to prescribe antimicrobials for URTIs. Correlation analysis showed that the level of physician's knowledge, attitude, and prescription practice is related ( P < .05). In conclusion, proper prescription of antimicrobials depends on adequate knowledge and regular training programs for physicians.